Effects of attentional bias research on understanding nature of craving and relapse - Türkoğlu, Sevgül (Journal of Dependence, 2024)
Addictive behaviors (substance use, craving, drug seeking behavior) are characterized by severe alcohol/substance use. People with addiction problems become more sensitive subtance related stimuli and they react excessive to the subtance related stimuli. This is called as attentional bias. Attentional bias occurs as impilicit/ automatic. Studies show that attentional bias plays an important role in substance craving and relapse. In this review, the reason of addiction attentional bias and its consequences was analyzed. In this frame, the attentional bias paradigms were explanied briefly. Because these paradigms are utilized as tool for attentional bias measurement. After that, the relationship between attentional bias and craving and the effect of attentional bias on relapse were summarizied. From this point it can be said that, alcohol/subtance attentional bias is positively related with craving and it can determinate the risk of relapse earlier. Attentional bias researches may benefit for treatment as usual. Because, researchers are suggested that, attentional bias is promising a usefull measurement tool to prevent the people with addiction problems from the craving and risk of relapse. However, being able to utilized attentional bias as a tool in the clinical field, it is needed to develop further theoretical knowledge and overcome methodological shortcomings.